Immunomodulatory activity and control of Salmonella Enteritidis colonization in the intestinal tract of chickens by Lactobacillus based probiotic - Penha Filho, Rafael Antonio Casarin [UNESP]; Díaz, Silvia Juliana Acelas [UNESP]; Fernando, Filipe Santos [UNESP]; Chang, Yung-Fu; Andreatti Filho, Raphael Lucio [UNESP]; Berchieri Junior, Angelo [UNESP] (Elsevier B. V., 2015)
Lactobacillus-based probiotics (LBP) are used as competitive exclusion to control pathogenic enterobacterial infections and improve the weight gain in broiler chickens. This study assessed the inhibition of Salmonella Enteritidis (SE) infection in one-week-old broiler chicks, using an experimental LBP containing four Lactobacillus strains isolated from chickens (L. acidophilus, L. fermentum, L. reuteri, L. salivarius). The immunomodulatory effects of this treatment were evaluated, through the analysis of cytokines and influx of macrophages, γδ, CD4(+) and CD8(+) T cells in the gut. The intestinal colonization by SE was reduced by 1.8CFU/g (log10) in chicks treated with LBP (p<0.05). The levels of pro-inflammatory cytokines (IL-1β, LITAF) were significantly reduced in treated chicks (p<0.05), whilst untreated chicks showed elevated inflammatory stimulus and an increased population of CD8(+) T cells in the intestinal mucosa after challenge (p<0.05). Additionally, the LBP stimulated TLR2 expression in caecal tonsils. The adjuvant property of the Lactobacillus cell wall (LCW) was evaluated, demonstrating good capability to stimulate T helper 2 (Th2) cell proliferation. Pretreatment of chicks with LBP decreased the intestinal colonization by SE, minimizing the tissue lesions and inflammation after challenge and showed a potential use as adjuvant with injectable killed vaccines.
Keywords: Adjuvant; Cytokine; Fowl paratyphoid; Macrophage; Tlr2; Vaccine